Two novel bimetallic transition metal–uranyl one‐dimensional coordination polymers with manganese(II) and cobalt(II) incorporating bridging diglycolate (2, 2′‐oxydiacetate) ligands. Issue 8 (6th July 2017) - Ridenour, J. August; Pyrch, Mikaela M.; Manning, Zachery J.; Bertke, Jeffery A.; Cahill, Christopher L.
Abstract : Novel uranyl bimetallic one‐dimensional coordination polymers containing cobalt and manganese have been synthesized and structurally analyzed via X‐ray diffraction techniques. The local and global structures of the two compounds have been compared and their photoluminescence properties have been analyzed. Abstract : The crystal structures of two new bimetallic uranyl–transition metal compounds with diglycolic acid [or 2‐(carboxymethoxy)acetic acid] have been hydrothermally synthesized and structurally characterized via single‐crystal X‐ray diffraction. The compounds, namely catena ‐poly[[[tetraaquamanganese(II)]‐μ‐2, 2′‐oxydiacetato‐[dioxidouranium(VI)]‐μ‐2, 2′‐oxydiacetato] dihydrate], [MnU(C4 H4 O5 )2 O2 (H2 O)4 ]·2H2 O n, and catena ‐poly[[[tetraaquacobalt(II)]‐μ‐2, 2′‐oxydiacetato‐[dioxidouranium(VI)]‐μ‐2, 2′‐oxydiacetato] dihydrate], [CoU(C4 H4 O5 )2 O2 (H2 O)4 ]·2H2 O n, both crystallize in the triclinic space group P . These compounds form one‐dimensional chains via alternating uranyl and transition metal building units. The chains then assemble into three‐dimensional supramolecular networks through several hydrogen bonds between water molecules and diglycolate ligands. Luminescence measurements were conducted and no uranyl emission was observed in either compound.